REFORMULASI UNDANG-UNDANG DARURAT NOMOR 7 TAHUN 1955 TERHADAP PERKEMBANGAN TINDAK PIDANA EKONOMI - Rizkydhio Putera Bermuda (2023)
Economic Crime originated from business ethics that developed outside the codification of the Criminal Code and is a criminal act with economic motives that has an influence on many aspects such as social, economic, political and cultural. Emergency Law Number 7 of 1955 which regulates economic crimes has not been renewed and has been left. Various types of criminal acts in the economic sector contained in the Law. No.7/drt/1955 has been regulated in its own law. Criminal acts in the economic sector are part of the economic law that applies in a country and cannot be separated from the economic system adopted by the nation. The development of increasingly sophisticated technology makes the modus operandi increasingly new and demands the need for updates to laws and regulations in the economic sector by conducting an inventory of laws and regulations related to economic crimes. Reformulation of the Law. No.7/drt/1955 also needs to be done by establishing effective sanctions policies in order to make economic activities conducive. This research uses normative juridical research methods using descriptive analysis techniques. The results of the study will discuss the development of economic crimes that exist in Indonesia today and reformulation of sanctions policies and determine the scope and terms of economic crimes.